61 tunneling company: South African miners in the Middle East during the Second World War - Kleynhans, Evert (My University, 2012)
The South African Engineering Corps (SAEC) provided a variety of specialised units to assist the Allies during the Second World War. These units performed outstanding work in the East and North African theatres, as well as in Italy. Through their concerted efforts, they were able to provide much needed assistance to the troops on the ground. South African engineering troops, however, served in lesser known territories as well. The likes of 61 Tunnelling Company, under the auspices of the Mines Engineering Brigade (MEB) SAEC, was but one of these specialised units called upon to render services to the Allied forces in the Middle East. The company, representing a cross-section of miners from the Witwatersrand, was tasked to dig a series of tunnels that continued to the completion of the Haifa-Beirut-Tripoli (HBT) railway line. Upon completion of the task, the unit further carried out two more tunnelling tasks in the Middle East, namely at Ras Bayada and at the Kasmieh Irrigation Scheme. Due to the specialised nature of this unit, its exploits during the war only received minimal attention in the written histories of the South African forces. This article thus explores the history of 61 Tunnelling Company’s exploits in the Middle East during the Second World War.
Keywords: 61 Tunnelling Company; Union Defence Force; South African Engineering Corps; Mines Engineering Brigade; Haifa-Beirut-Tripoli railway; Cheka tunnel; Ras Bayada; Kasmieh irrigation scheme